1983
DOI: 10.1177/030098588302000306
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Dysplasia of English Springer Spaniel Dogs: Light Microscopy of the Postnatal Lesions

Abstract: Abstract. The histologic features of retinal dysplasia were studied in 26 English springer spaniel dogs of one day to four years of age. Dysplastic lesions in neonatal pups occurred predominantly in the peripapillary tapetal area of sensory retina. They consisted of complex linear folds and rosettes which were composed of hyperplastic neuroblasts. Dysplasia usually was not associated with incomplete differentiation of the outer neuroblastic layer. The outer limiting membrane was absent locally and numerous pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Retinal dysplasia has been described as an inherited condition in several breeds of dog . In this paper, we report the establishment of a breeding colony to study RD identified in American pit bull terriers, a breed in which the condition has not previously been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Retinal dysplasia has been described as an inherited condition in several breeds of dog . In this paper, we report the establishment of a breeding colony to study RD identified in American pit bull terriers, a breed in which the condition has not previously been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting lesions range in severity from multifocal RD, where histologically there is folding of retinal layers or duplication of one or more retinal neuronal layers, to more severe lesions including larger geographic regions of retinal malformation or even retinal detachment or nonattachment . RD has been reported as an inherited trait in several breeds of dog but may also result from environmental insults during retinal development including infection (e.g., canine herpesvirus), toxicity (e.g., vitamin A deficiency), and intra‐uterine irradiation . In most instances, lesions are present and detectable on examination of puppies at a few weeks of age, although one survey of dogs bred as leader dogs reported that lesions could develop or become apparent after the age at which the retina is mature …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the lesions typical of rd may become visible at different life stages. In a study by O'Toole et al (1983), dysplastic lesions in English Springer Spaniels were detected in an ophthalmoscopic examination straight after birth, whereas Holle et al (1999) found that in the case of geographic retinal dysplasia, the lesions were rarely noticeable earlier than week 10 of life, which may be associated with tapetal development which can last for up to the first 6 months of life (Cook 2013). It has been noted that single or multiple retinal folds may become less visible with age (Grahn et al 2004) or may disappear completely, after which the fundus returns to normal (ACVO Genetics Committee 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that single or multiple retinal folds may become less visible with age (Grahn et al 2004) or may disappear completely, after which the fundus returns to normal (ACVO Genetics Committee 2014). This is most probably associated with a redevelopment of the retina (O'Toole et al 1983;Cispin et al 1999;Holle et al 1999;Grahn et al 2004). Furthermore, because an ophthalmoscopic examination is subjective in nature, it gives rise to differences in how the fundus is evaluated.…”
Section: Discussionmentioning
confidence: 99%